A case report of primary neuroendocrine carcinoma of the perihilar bile duct. Issue 1 (December 2015) - Kihara, Yasuhiro; Yokomizo, Hiroshi; Urata, Takahiro; Nagamine, Michiko; Hirata, Toshihiko
Abstract Background Although neuroendocrine tumors are most commonly found in the digestive system, neuroendocrine tumors originating from the bile duct are rare, and neuroendocrine carcinomas derived from the perihilar bile duct are extremely rare. This report presents the clinical course and clinicopathological features of neuroendocrine carcinomas arising from the extrahepatic bile duct. Case presentation A 70-year-old Japanese woman was preoperatively diagnosed with perihilar cholangiocarcinoma, and a radical resection with an extended left hepatic lobectomy and a choledochojejunostomy was performed. From the histopathological findings, we diagnosed the tumor as a neuroendocrine carcinoma of the bile duct (small cell type) with lymph node metastasis. The patient was treated with the same adjuvant chemotherapy as that used for small cell carcinoma of the lung. At 10 months after surgery, there was no recurrence of the disease. Conclusion Neuroendocrine carcinoma of the extrahepatic biliary tracts is a very rare and highly malignant disease with a poor prognosis. A multidisciplinary approach could improve the prognosis for this neoplasm.